Organizational Patient Safety Culture, Psychological Resilience, and Job Satisfaction Among Nurses in ISO-Certified and Non-ISO-Certified Departments: An Exploratory Cross-Sectional Comparison - Georgios Manomenidis; Konstantinos Gkotsidis; Savvato Karavasileiadou; Vasiliki Georgousopoulou (Healthcare, 2026)
Background/Objectives: ISO-based quality-management systems may be associated with organizational processes relevant to patient safety, but evidence regarding nurses’ safety-culture perceptions, resilience, and job satisfaction remains limited. This study compared nurses working in ISO-certified and non-ISO-certified hospital departments. Methods: This cross-sectional study included 263 nurses from 29 departments (11 ISO-certified and 18 non-ISO-certified) in one tertiary hospital in Northern Greece. Patient safety culture was assessed using the 10 dimensions of the Hospital Survey on Patient Safety Culture 2.0, together with the Brief Resilience Scale and Job Satisfaction Index. Unadjusted comparisons and covariate-adjusted linear regression models with heteroscedasticity-robust standard errors were performed, with Benjamini–Hochberg false-discovery-rate correction. Results: In unadjusted analyses, nurses working in ISO-certified departments reported higher Staffing and Work Pace (MD = 0.222, 95% CI [0.094, 0.351], g = 0.40) and Reporting Patient Safety Events (MD = 0.427, 95% CI [0.134, 0.719], g = 0.37), but lower Handoffs and Information Exchange (MD = −0.295, 95% CI [−0.458, −0.131], g = −0.45); all three differences remained significant after false-discovery-rate correction. Resilience and job satisfaction did not differ in unadjusted analyses. After adjustment and correction, working in an ISO-certified department was associated with higher Staffing and Work Pace, Supervisor/Manager/Clinical Leader Support, and job satisfaction, and with lower Hospital Management Support and Handoffs and Information Exchange; no association with resilience was observed. Conclusions: Working in ISO-certified departments showed selective, modest, and mixed nurse-reported associations. Because certification was a department-level characteristic and within-department clustering could not be modeled, the findings should be interpreted as exploratory rather than as estimates of a department-level certification effect.